1998
DOI: 10.1086/514275
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Varicella in France: A Study in Day Care Centers

Abstract: To assess the cost of varicella in young children in France, a prospective study was done in day care centers. Children (1263), who were 3 months to 3 years old and attending day care, were followed over a varicella season. For every child who developed varicella (n = 200), detailed information was obtained by use of parental questionnaires. Questions concerned medical care, days missed from work for parents, and the need for extra baby-sitting. On average, each sick child had one consultation with a physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
10
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
5
10
0
1
Order By: Relevance
“…The estimated percent of children with varicella seen by a physician for each year of age for 0-6 years were 57, 48, 32, 21, 22, 27 and 30 %. These estimates fit the reported data for frequency of physician visits for children with chickenpox [25][26][27][28]. Similar estimates for those over 7 years of age were derived from the literature assuming that all individuals contract varicella during their lifetime [1,29].…”
Section: Force Of Infection Of Varicellasupporting
confidence: 71%
“…The estimated percent of children with varicella seen by a physician for each year of age for 0-6 years were 57, 48, 32, 21, 22, 27 and 30 %. These estimates fit the reported data for frequency of physician visits for children with chickenpox [25][26][27][28]. Similar estimates for those over 7 years of age were derived from the literature assuming that all individuals contract varicella during their lifetime [1,29].…”
Section: Force Of Infection Of Varicellasupporting
confidence: 71%
“…The estimated percent of children with varicella seen by a physician for each year of age for 0-6 years were 57, 48, 32, 21, 22, 27 and 30 %. These estimates fit the reported data for frequency of physician visits for children with chickenpox [25][26][27][28]. Similar estimates for those over 7 years of age were derived from the literature assuming that all individuals contract varicella during their lifetime [1,29].…”
Section: Force Of Infection Of Varicellasupporting
confidence: 70%
“…The lowest value (0.6 days) was reported for the first time by Banz et al 42 , estimated from an epidemiological survey in Germany. Brisson & Edmunds 43 presented the same figure (0.6 days) based on epidemiological studies in Europe 35,36,53 , and Coudeville et al 48 and Hammerschmidt et al 52 used the same estimate initially reported by Banz et al 42 . The highest value (5 days) came from an assumption in the first economic evaluation study on the varicella vaccine 32 , in 1994.…”
Section: Results Of Literature Searchmentioning
confidence: 65%
“…While some authors 48,52 repeated the value (0.6 days) initially reported by Banz et al 42 or presented the same value 43 as in epidemiological studies conducted in Europe 35,36,53 , others assumed a higher figure (5 days). It was not surprising that the highest percentage of indirect costs in the total cost of varicella (98%) 34 was associated with the second highest cost of a workday (PPP$316.90).…”
Section: Discussionmentioning
confidence: 71%